Interactions between proteins and partial acylglycerols at oil-water and air-water interfaces of partially crystalline emulsions: Interfacial structure, adsorption, and foaming behavior - Xie, Pengkai; Lai, Junqi; He, Tong; Zhou, Jun; Mao, Yilin; Lee, Yee Ying; Tan, Chin Ping; Hong, Shyang Pei; Wang, Yong; Zhang, Zhen (Elsevier B.V., 2025)
This study developed and elucidated a mechanism by which milk protein–lipid interactions at both the oil–water (O/W) and air–water (A/W) interfaces govern the stability of partially crystalline emulsions (PCEs) and their foams. At the O/W interface, compared with conventional triacylglycerol (TAG)–based PCEs formulated with palm kernel stearin (PKST) as the crystallizing fat, fat crystals of partial acylglycerols in the diacylglycerol (DAG) form increased interfacial polarity and strengthened hydrogen-bonding and hydrophobic interactions with adsorbed milk proteins, thereby modulating surface potential and reducing Brownian motion, which in turn enhanced the long-term emulsion storage stability. QCM-D corroborated at the microscale that DAG-based fat crystals, upon tight association with milk proteins, increase the viscoelasticity of the interfacial membrane. Building on this, the consequences of milk protein–lipid interactions at the A/W interface during the foam-formation stage were further evaluated. Bubble-dynamics experiments indicated that DAG–protein co-adsorption accelerates film formation and yields cooperative films with lower interfacial tension and higher elasticity. Concomitantly, DAG-type fat crystals markedly reduce bubble–crystal adhesion, facilitating rapid bubble encapsulation, slowing bubble escape, and increasing gas hold-up, thereby improving foamability and foam stability. Whipping-kinetics analyses and cryo-SEM consistently substantiated that DAG–protein interactions favor the rapid establishment and robustness of A/W interfacial membranes. Notably, even at identical solid fat content (SFC), altering the fat-crystal type profoundly changes the O/W and A/W behaviors of PCEs. Taken together, these findings delineate an interfacial-engineering strategy that modulates protein–lipid interactions to control the formation and stability of emulsions and foams, offering guidance for the development of clean-label, high-performance PCEs with reduced saturated fat.